Lie-Symmetry Analysis of Couple-Stress Fluid Flow and Heat Transfer Past in a Bidirectional Moving Sheet - Mandal, Bidyut (Journal of Applied Nonlinear Dynamics, 2026)
This work explores the steady boundary layer flow and heat transfer of a couple-stress fluid flowing over a bidirectional movable surface. The Lie group of symmetry transformations are employed for determining the possible invariant solutions of the governing equations for fluid flow and heat transfer. The self-similar equations are solved numerically and plotted graphically. It is observed that fluid velocities in both $x$ and $y$ directions increase due to the increase of the couple-stress parameter. The stretching ratio parameter suppresses the flow boundary layer in the $x$-direction, but it extends in the $y$-direction. The thermal boundary layer thickness reduces for increasing values of couple stress parameter, stretching ratio parameter, Prandtl number, and power-law index parameter on wall temperature, but opposite behavior occurs for radiation parameter.